2016
DOI: 10.1016/j.susc.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Early and transient stages of Cu oxidation: Atomistic insights from theoretical simulations and in situ experiments

Abstract: Understanding of metal oxidation is critical to corrosion control, catalysis synthesis, and advanced materials engineering. Although, metal oxidation process is rather complicated, different processes, many of them coupled, are involved from the onset of reaction. Since first introduced, there has been great success in applying heteroepitaxial theory to the oxide growth on metal surface as demonstrated in the Cu oxidation experiments. In this paper, we review the recent progress in experimental findings on Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 144 publications
(228 reference statements)
2
33
0
Order By: Relevance
“…[11][12][13] Using ex situ energy-dispersive Xray spectroscopy (EDS), Cuenya and co-workers reported that al arge fraction of the initial oxide can be resistant to reduction even under strongly reducing potentials typically used for CO 2 R. [11,12] They proposed that the presence of Cu + on the surface was important for the formation of C 2 /C 3 products. [19][20][21][22][23] It is therefore possible that OD Cu can rapidly reoxidize,a nd as ar esult the O content characterized ex situ would not be representative of the actual case during CO 2 R.To address these concerns,w ee mployed 18 Oi sotope labeling to confirm the presence/absence of residual oxides in OD Cu during CO 2 R. 18 Oe nriched OD Cu catalysts were synthesized by oxidation/reduction cycling in H 2 18 Ofollowing the procedure of Nilsson and co-workers (see the Supporting Information for full details). [14] First-principles calculations performed by Goddard and co-workers found that the presence of oxygen in the subsurface would generate am ix of Cu + and Cu 0 on the surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Using ex situ energy-dispersive Xray spectroscopy (EDS), Cuenya and co-workers reported that al arge fraction of the initial oxide can be resistant to reduction even under strongly reducing potentials typically used for CO 2 R. [11,12] They proposed that the presence of Cu + on the surface was important for the formation of C 2 /C 3 products. [19][20][21][22][23] It is therefore possible that OD Cu can rapidly reoxidize,a nd as ar esult the O content characterized ex situ would not be representative of the actual case during CO 2 R.To address these concerns,w ee mployed 18 Oi sotope labeling to confirm the presence/absence of residual oxides in OD Cu during CO 2 R. 18 Oe nriched OD Cu catalysts were synthesized by oxidation/reduction cycling in H 2 18 Ofollowing the procedure of Nilsson and co-workers (see the Supporting Information for full details). [14] First-principles calculations performed by Goddard and co-workers found that the presence of oxygen in the subsurface would generate am ix of Cu + and Cu 0 on the surface.…”
mentioning
confidence: 99%
“…1) Cu nanomaterials have been shown to readily oxidize,which could create difficulties in performing accurate ex situ quantification of the oxygen content; [17,18] 2) Moisture and oxygen are known to cause corrosion (oxidation) of Cu and exposure to both is difficult to avoid;corrosion might also be exacerbated in aporous,high surface area material such as OD Cu;3 )ODC up ossesses ah igh density of grain boundaries,w hich are known to accelerate the oxidation process by serving as nucleation sites and as pathways where diffusion can occur at afaster rate. [19][20][21][22][23] It is therefore possible that OD Cu can rapidly reoxidize,a nd as ar esult the O content characterized ex situ would not be representative of the actual case during CO 2 R.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This work aims to establish a correlative investigation utilizing theory and in situ ETEM in tandem to bridge the spatial and temporal gaps between experimental and computational approaches. Initially focusing on the oxidation of copper (a well-studied model system for metal oxidation) [1], ultimately this work aspires to develop a continuous and precise predictive model of oxidation across all studied scales of measurement.We investigated the Cu 2 O island nucleation preference sites (edge or terrace) using both experiment and theory for three low index ((001), (011), and (111)) copper film surfaces (~70 nm thick) were grown via ultra-high vacuum electron-beam evaporation on a NaCl crystal of a specific orientation. These single crystalline Cu films were annealed in situ using a Hitachi H9500 ETEM equipped with a double-tilt heating holder (T max = 1000 °C) -to produce faceted holes of pristine Cu surfaces -using a hydrogen atmosphere (1x10 -3 Torr H 2 ).…”
mentioning
confidence: 99%
“…This work aims to establish a correlative investigation utilizing theory and in situ ETEM in tandem to bridge the spatial and temporal gaps between experimental and computational approaches. Initially focusing on the oxidation of copper (a well-studied model system for metal oxidation) [1], ultimately this work aspires to develop a continuous and precise predictive model of oxidation across all studied scales of measurement.…”
mentioning
confidence: 99%